Co‐infection of dengue, scrub typhus, and typhoid during dengue outbreak in Nepal, 2022: A case report - Bibek Raj Bhattarai; Rajshree Bhujel; Sushant Pokhrel; Abhishek Mishra; Anamika Priyadarshinee (Clinical Case Reports)
Abstract In midst of the recent dengue outbreak in Nepal, in 2022, the risk of co‐infection increases and may lead to fatal outcomes if the diagnosis of multiple infections is delayed. Thus, all available diagnostic approaches must be taken to decrease the burden of illness and lessen mortality.